The possible formation of speculative bubbles after the last economic crisis and their impact on investors - Novotný Josef (Gaudeamus, 2015)
This article deals with the problem of speculative bubbles which may occur in financial markets after the last financial crisis, including their impact on investors. Speculative, or sometimes also called price bubbles, are part of a psychological analysis of financial markets. From time to time these undesirable bubbles appear in some types of investment instruments in financial markets. The aim of this article is to identify those areas of investment instruments where these types of bubbles can occur in the future. The main problem which appears here is to detect the possible formation of new speculative bubbles. If these bubbles are eliminated in advance, it will have a positive impact not only for investors but also for the whole economy of some countries.
Možný vznik spekulativních bublin po poslední ekonomické krizi a jejich vliv na investory
Keywords: Speculative bubbles; investor; economic crisis; financial markets; creditor; Spekulativní bubliny; investor; ekonomická krize; finanční trhy; věřitel